2022
DOI: 10.3390/cells11111836
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value and Molecular Function of Circulating MicroRNAs in Endometrial Cancer Regulation: A Systematic Review

Abstract: This systematic review of literature highlights the different microRNAs circulating in the serum or plasma of endometrial cancer patients and their association with clinical and prognostic characteristics in endometrial cancer. This study also investigates the molecular functions of these circulating microRNAs. According to this systematic review, a total of 33 individual circulating miRs (-9, -15b, -20b-5p, -21, -27a, -29b, -30a-5p, -92a, -99a, -100, -135b, -141, -142-3p, -143-3p, -146a-5p, -150-5p, -151a-5p,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…However, discordant results might allow for the consideration of an active mechanism that, if further supported by the data, might shed light on new and interesting features of miR biology in EC. [86] and Delangle and collaborators [85]. The former study (red circle) identified 33 different miRs deregulated in EC; the second (blue circle) identified 139 miRs; 16 miRs are reported in both publications.…”
Section: Using Circulating Mirs For Ec Diagnosismentioning
confidence: 96%
See 2 more Smart Citations
“…However, discordant results might allow for the consideration of an active mechanism that, if further supported by the data, might shed light on new and interesting features of miR biology in EC. [86] and Delangle and collaborators [85]. The former study (red circle) identified 33 different miRs deregulated in EC; the second (blue circle) identified 139 miRs; 16 miRs are reported in both publications.…”
Section: Using Circulating Mirs For Ec Diagnosismentioning
confidence: 96%
“…However, the possibility to use circulating miRs to achieve this characterization is still under evaluation and has been only poorly explored in EC. In 2022, Bloomfield and collaborators performed a systematic review in search of circulating miRs in the serum and plasma of EC patients [86]. Their analysis allowed identifying 33 significantly deregulated miRs (Figure 2), 27 up-and 4 down-regulated, while the remaining 2 (miR-21 and miR-204) showed contradictory expression values, depending on the study considered (Table 1).…”
Section: Using Circulating Mirs For Ec Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey showed that a total of 33 circulating miRNAs and six different panels of circulating miRNAs have been described for their diagnostic performance in EC diagnosis. A total of seven circulating miRNAs and one panel of circulating miRNAs have been associated with clinical and prognostic factors in EC ( 93 ). In a variety of tumor studies, significant progress has been made in the use of ncRNAs in extracellular fluid as cancer biomarkers ( 94 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The review revealed significant expression differences in EC patients compared to healthy individuals. However, on another hand, more studies should be conducted to better understand the function and circulation of these miRs [5]. The relevance of microRNA (miRNA) in the development and spread of colon cancer has, furthermore, been highlighted.…”
mentioning
confidence: 99%